PERBANDINGAN TITER ANTIBODI AYAM BROILER YANG DIVAKSIN PADA UMUR 7 DAN 14 HARI MENGGUNAKAN VAKSIN AVIAN INFLUENZA HETEROLOG SUBTIPE H5N2 - Ukon Susetyo; Michael Haryadi Wibowo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2008)
The aim of this study was to compare the titer antibody respons induced by different vaccination programusing heterologous avian influenza H5N2 subtype at day seven and 14 in broiler chicken. A number of 120broiler chickens was divided into three groups, each consisted of 40 birds and kept since day old chicken instandard maintenance facilities. Group one as the treatment group was vaccinated at 7 days of age usingheterologous vaccine H5N2 subtype. The second group was vaccinated at 14 days of age using the samevaccine. The control group, received no vaccination. A number of24 birds in each group were randomly chosenand bled via brachialis vein at day 14, 21 and 28 post vaccination, respectively. The antibody titer in the serawas measured using hemaglutination inhibition (HI) test with homologous antigen H5N2 subtype. Data wereanalysed using a split-plot design of analysis of variance of 0,05, significance level. The titer induced by vaccinationat day-7 were 1,54; 15,92 and 6,58 HI unit, respectively. Meanwhile in the second group the titer obtained were1,29; 7,38 and 15 HI unit respectively. Antibody of the control group was negativ. Further analysis indicated thatthere was significance different antibody titer induced by vaccination between treatment groups, but whencompared between group of treatment, the result showed po significance different.Keys words: avian influenza. broiler chicken, heterologous vaccine, and antibody titer